Self-Efficacy and choice actions in STEM disciplines among students: A Systematic Review - Perla Guadalupe (2025)
Currently, globalization highlights the growing interest in understanding the factors that influence students' choice of STEM careers. Factors such as self-efficacy and choice actions play a decisive role in professional decision-making. The objective of this article was to identify the existing literature on the relationship between self-efficacy and choice actions among students selecting STEM disciplines. A literature search was conducted in five databases: SciELO, Redalyc, DOAJ, SCOPUS, and Google Scholar, using thesauri and Boolean operators in both Spanish and English. 72.5% of the studies included in this article were published between 2020 and 2023, with the United States leading in the number of investigations, followed by China and Mexico. Most of the research focused on the university level, identifying key variables such as attitude, outcome expectations, and intrinsic motivation. Findings indicate that students with higher self-efficacy are more likely to choose and persist in STEM disciplines. It is concluded that there is a significant research gap concerning high school and secondary school students, particularly in Mexico, suggesting the need for further studies at these educational levels.